Fatigue among psoriatic arthritis patients: validity of the Arabic version of the FACIT-F questionnaire - Shymaa A. Sarhan; Noha Ehab; Enas M. Mekkawy (Egyptian Rheumatology and Rehabilitation)
Abstract Background Fatigue is a prominent complaint in psoriatic arthritis (PsA). The Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) Scale is considered a self-reported measure commonly employed for evaluating fatigue in individuals with PsA. Aim The study aims to focus on the effects of fatigue on the daily functioning of PsA patients and assess the content validity and reliability of the Arabic version of the FACIT-Fatigue Scale among PsA patients. Methods Using the FACIT-F Scale, PsA patients who consistently visited the outpatient clinic underwent two evaluations at a 2-week interval. Patients got comprehensive clinical assessments. Cronbach’s α was employed to evaluate the internal consistency of different items, the interclass correlation coefficient (ICC) was utilized for evaluation of test–retest reliability, also for detection of the association between the FACIT-F scores and other disease activity measures and disease manifestations was studied to establish validity. Results Among the total studied 54 PsA patients, 35.2% exhibited fibromyalgia. Patients with fibromyalgia reported decreased FACIT-F scores compared to those without fibromyalgia (19.4 ± 2 versus 25.5 ± 2.9, respectively) (P = 0.01). An assessment was carried out to evaluate the test–retest repeatability of the Arabic version of the FACIT-F. The results showed an acceptable ICC value of 0.70, indicating good reliability and a strong internal consistency of 0.93. The FACIT-F questionnaire revealed strong positive correlations with the SF-36 questionnaire and inverse correlations with the PsA-QoL questionnaire, demonstrating its convergent validity. FACIT-F Scale showed a moderate negative significant correlation with tender and swollen joint total count. Also, there was a strong negative correlation between BASDAI and DASPSA scores. ROC curve for distinguishing PsA patients with and without fibromyalgia was conducted and revealed that the FACIT-F score had good discriminating power, with an AUC of 0.86, sensitivity (of 69.7%, and specificity of 94%. Conclusion The reproducible Arabic version of the FACIT-Fatigue Scale was well-correlated with activity parameters and other fatigue scales among PsA patients. Thus, the FACIT-Fatigue Scale is a reliable and valid tool for assessing fatigue among PsA patients.